2017
DOI: 10.1016/j.joto.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Auditory symptoms and psychological characteristics in adults with auditory processing disorders

Abstract: Most adults with auditory processing disorder (APD) often have trouble at work. It is possible that these listening problems in adults with APD influence their mental health. Thus, we have to take the subject's personality and mental status into consideration when supporting subjects with APD. However, studies on APD in adults are comparatively rare. In this study, we aimed to evaluate the relationships between the results of auditory tests, APD symptoms, and psychological status in subjects with APD. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
2
10
0
2
Order By: Relevance
“…Firstly, the backward digit span test’s performance demonstrated that executive function, more specifically, working memory, is impaired in the LDG. This finding supports previous research that revealed a link between executive function and listening difficulties [ 7 , 8 , 10 , 42 , 43 ]. Several studies have demonstrated not only the poor performance of children with listening difficulties in cognitive tests (including working memory tests), but also the cognitive performance as the best predictor of poor listening [ 7 , 8 , 10 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Firstly, the backward digit span test’s performance demonstrated that executive function, more specifically, working memory, is impaired in the LDG. This finding supports previous research that revealed a link between executive function and listening difficulties [ 7 , 8 , 10 , 42 , 43 ]. Several studies have demonstrated not only the poor performance of children with listening difficulties in cognitive tests (including working memory tests), but also the cognitive performance as the best predictor of poor listening [ 7 , 8 , 10 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…The responses obtained through the current questionnaire also indicate that, even when the main concern involves listening skills, memory and attention issues might also be present. The only study which investigated cognitive skills in adults with listening difficulties also indicated a low score in an auditory memory test [ 43 ], corroborating the current findings.…”
Section: Discussionsupporting
confidence: 88%
“…Some children with APD have reported relying more on anger regulation and less on problem-solving as a coping strategy, but in the reported study, the sample size was small ( N = 20) ( 23 ). Adults with APD similarly focus on restraining their emotions rather than on self-directed thinking ( 23 , 24 ). APD in childhood may also affect the “sense of self” into early adulthood ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] Another important issue is the testing of senior citizens (>60 years of age). This population has the highest incidence of APD, 5,7 and it could be crucial to quantify how performance in the tests described here progresses in advanced age as well as quantifying the benefits of therapeutic procedures such as ACAT in older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…1 Around 3% of children and 70% of elderly people exhibit these disorders, which can lead to severe impairments in learning, speech, attention, and memory. [4][5][6][7] Auditory processing disorder is traditionally diagnosed by acoustically controlled hearing tests, such as the filtered speech tests (FSTs) and the binaural resynthesis test (BRT). They force the central nervous system to reconstruct a verbal message by reducing information redundancy in speech signals using filtering.…”
mentioning
confidence: 99%